Yeast Protocols Methods in Cell and Molecular Biology - Evans, Ivor H.; Evans, Ivor H. (Methods in Molecular Biology,, 1996)
Yeast Protocols intends to offer a selection of well-proven proto cols in cell and molecular biology, applicable to yeasts including, but certainly not exclusively aimed at, Saccharomyces cerevisiae. Saccharomyces cerevisiae and its very distant cousin, Schizosacc- romyces pombe, are of course now foremost model eukaryotic organisms, and the focus of wide-ranging experimental studies, especially those using molecular genetic techniques. Many of the lat ter, such as DNA sequencing and in vitro mutagenesis, are general DNA techniques, well covered in other volumes of Humana's Meth ods in Molecular Biology series, and elsewhere. The inclusion of a number of non-DNA techniques in this book is meant to reflect the resurgent interest in yeast cell biology sparked by the development of gene manipulation methods—for example, cellular localization of cloned gene products using microscopical techniques. The presentation of protocols follows the successful Methods in Molecular Biology series format, with a clear sequence of steps and extensive troubleshooting notes. It is our hope that these protocols will be useful not only to established members of the full-time research community, but also to the less experienced—first degree level and masters students undertaking project work, as well as PhD students starting their experimental programs; I am well aware that these young apprentice scientists are not always able to receive the supervision time that they, and indeed their supervisors, would like.